2002
DOI: 10.1136/oem.59.11.734
|View full text |Cite
|
Sign up to set email alerts
|

Lead induced increase of blood pressure in female lead workers

Abstract: Aims: Although lead exposure has, in the absence of mathematical modelling, been believed to elevate blood pressure in females, it is necessary to clarify the relation between lead and blood pressure by eliminating confounding factors in the analysis. Methods: Blood lead was measured in 193 female workers, including 123 lead exposed workers. Possible confounding factors were controlled by multiple regression analyses. Results and Conclusion: Blood lead above 40 µg/dl was found to be the most potent factor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The role of Pb as an occupational pollutant stressor for elevated blood pressure could well be confounded by the presumed role of other risk factors such as age, BMI, alcohol consumption, smoking habits, HCT, plasma trigliceride and cholesterol [16][17][18] .…”
Section: Relationship Of Blood Lead Levels To Blood Pressure 307mentioning
confidence: 99%
“…The role of Pb as an occupational pollutant stressor for elevated blood pressure could well be confounded by the presumed role of other risk factors such as age, BMI, alcohol consumption, smoking habits, HCT, plasma trigliceride and cholesterol [16][17][18] .…”
Section: Relationship Of Blood Lead Levels To Blood Pressure 307mentioning
confidence: 99%
“…Perry et al [2] demonstrated in rats exposed to lead in amounts comparable to the environmental lead exposure to human beings had an average elevation in systolic pressure comparable to that of human beings. Studies conducted by Nomiyama et al [3] demonstrated that blood lead above 40 lg/dl was found to be the most potent factor for elevating systolic/diastolic blood pressure. Their data suggested that lead induced changes in lipoprotein metabolism that play an important role in the lead induced increase in blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature have suggested an association between high levels of blood lead and high BP in different categories of workers exposed, such as: police officers 8) , welders and PVC-workers (polyvinyl chloride) 9) , industrial workers and subjects exposed to vehicle smoke 10) , workers in the metal industry or other industrial activities 11) . The hypertension following lead exposure may be due to a higher secretion of renin by cells of the iuxtaglomerular apparatus 7) and/or to an alteration in plasma lipoprotein 12) . Kotseva e Popov (1998) have evaluated BP values at rest in workers exposed to benzene, toluene and xylene: systolic and diastolic BP values were significantly higher in exposed workers than in controls 13) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animals and human subjects have suggested that urban pollutants may alter blood pressure (BP) values; these agents are cadmium [1][2][3][4][5] , lead [6][7][8][9][10][11][12] benzene, toluene and xylene 13,14) . Besides these, physical agents such as noise [15][16][17][18][19] and psycho-social stressors [20][21][22][23] could alter BP values.…”
mentioning
confidence: 99%